We Did It! A Collaborative Collection Development Project at the KU and KSU Libraries - Currie, Lea; Greene, Mira E. (My University, 2017)
For many years, the KU and KSU Libraries have looked for a method of combining their resources to create a collaborative collection development project. When KSU joined YBP as their main book vendor, it became evident that such a project might get off the ground since KU Libraries were longtime customers of YBP. Since Proquest was the main vendor for e-books for both schools and YBP sold e-books from Proquest, KU and KSU decided to approach their e-book specialist with Proquest to find out if a collaborative demand-driven (DDA) e-book project was possible. During our first meeting with Proquest, it was decided that choosing a common list of publishers would be the best approach and Proquest set off to negotiate with eight of our most popular publishers. Sadly, that list dwindled down to four publishers who were willing to offer us a DDA program. There was still much to work out with Proquest and YBP before the new DDA project could go into effect. Our agreement with Proquest was to set up a DDA program with short-term loans and when a purchase was triggered, KU and KSU would together pay 150% of the list price for an e-book and both schools would have access no matter which school triggered the purchase. Proquest was planning to migrate EBL and Ebrary into a common platform called Proquest E-Book Central, so we decided to wait until that migration and all of the issues related to it were resolved.
Citation: Currie, Lea & Greene, Mira. (2017). We Did It! A Collaborative Collection Development Project at the KU and KSU Libraries. College & University Libraries Section (CULS) Conference, Kansas Library Association, Lawrence, KS.
Keywords: eBooks; Collection Development; Demand Driven Acquisitions (DDA); Collaborative; ProQuest; Patron Driven Acquisitions (PDA)